Rancang Bangun E-Commerce Untuk Penjualan Berbasis Web Pada Toko Nathan Flowers - Nathania Putri1, Nathania; Agustina, Asri Widya; Balqi, Siti Fadillah; Purnama, Iwan (Himpunan Dosen Gemilang Indonesia (HDGI), 2024)
Current development in science and technology provide convenience for humans in various matters, including transaction and trade. Throught the internet, tarde can offers their product online to buyerrs without needing to meet face to face from the result of the analysis of the running system in the sales procrss,anidea was proposed in the from of a web-based e-commerce design to overcome obstacles and problems related to promotional activities, transaction and making repots. With E-Commerce, transaction can take place quickly and costs more efficiently, thereby increasing the company’s bility to compete. One of them is by designing a website based marketing strategy. The e-commerce website that is built can increase sales, expend promotions, and make transactions easier. The results of selling and marketing product through the website provide many financial benefits as well as a high number of buyers and a wide product marketing area and it can be stated that the application of E-Commerce knows no time and space, it can be done anytimeand anywhere.